Migrant Remittances and Information Flows: Evidence from a Field Experiment* - Batista, Cátia (2014)
Do information flows matter for remittance behavior? We design and implement a randomized control trial to quantitatively assess the role of communication between migrants and their contacts abroad on the extent and value of remittance flows. In the experiment, a random sample of 1,500 migrants residing in Ireland was offered the possibility of contacting their networks outside the host country for free over a varying number of months. We find a sizable, positive impact of our intervention on the value of migrant remittances sent. Our results exclude that the remittance effect we identify is a simple substitution effect. Instead, our analysis points to this effect being a likely result of improved information via factors such as better migrant control over remittance use, enhanced trust in remittance channels due to experience sharing, or increased remittance recipients’ social pressure on migrants.